PERLINDUNGAN HAK PENYANDANG DISABILITAS DALAM PERSPEKTIF SOSIOLOGI HUKUM - Malik, Deden Abdul; Ningrum, Novita Ardiyanti; Zulvia, Ransya Ayu; Alfani, Feralda Septya; Aisah, Putri Maharani Rahma; Saebani, Beni Ahmad (Legal Standing : Jurnal Ilmu Hukum, 2024)
Protection of the rights of persons with disabilities in Indonesia is generally regulated through various statutory regulations, one of which is Law Number 8 of 2016 concerning Persons with Disabilities. However, various challenges arise due to stigma, discrimination and a lack of public understanding of the rights of people with disabilities.. The aim of this research is to determine the factors that cause social stigma towards people with disabilities, to determine efforts to overcome social stigma towards people with disabilities and legal protection. The methodology used in this research is juridical-empirical law with a qualitative paradigm with a legal sociology approach. Factors that cause social stigma towards people with disabilities are not receiving support from their families, a lack of self-will to develop, as well as negative stigma from society. Efforts to overcome social stigma towards people with disabilities include that the families of people with disabilities must provide support, people with disabilities must have the self-confidence to develop, and the community is given education through outreach regarding the prohibition of discrimination against people with disabilities.